High speed aerodynamics and flow control using porous plates - Moreno, Miguel (Cranfield University, 2024)
The integrated design of supersonic intakes and flow control systems is critical for stable aero-engine operation across various flight conditions. Porous bleed systems play a key role in mitigating shock wave-boundary layer interactions, improving intake efficiency and stability range by removing the low-momentum portion of the incoming boundary layers. However, accurately simulating intakes with fully resolved bleed systems using computational fluid dynamics is costly, and existing porous wall models often lack the complexity to capture the intricate physics of bleed flows, limiting their predictive accuracy. This research aims to enhance the aerodynamic understanding of porous plates with 90-degree bleed holes and to develop a refined porous wall model. Steady-state simulations were used to analyse porous plates under varying conditions, including different domain geometries, shock positions, and operating regimes. Using the computational database generated from these simulations, a model using local performance characteristics of individual bleed holes was developed. Additionally, a surface model was formulated to account for the flow field at the inflow of each bleed hole, enabling the computation of features such as capture streamtubes, shock topologies, and separation patterns. The proposed porous wall model was implemented in ANSYS CFX using MATLAB and benchmarked against existing approaches from the literature. The results of this comparison demonstrate major improvements over existing porous wall models, particularly during choked suction and within shock-affected regions. By incorporating discrete bleed actuation regions, local performance metrics, and accurate flow profiles at each hole, the proposed bleed model recreates the results of the simulation campaign and addresses major limitations of existing models, improving their flowfield predictions by a 13.5% on average.
MacManus, David G. - Associate Supervisor
Keywords: Porous; Bleed; Supersonic; Inlets; SWBLIs; domain geometries